Budget Impact Analysis of Ferric Derisomaltose for the Treatment of Iron-Deficiency in Malaysia - Chong, Huey Yi; Choon, June Wai Yee; Ang, Wei Chern; Lee, Kenneth Kwing Chin (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Untreated iron deficiency (ID) can lead to severe anaemia, requiring blood transfusion, or increased mortality risk. Globally intravenous (IV) iron is increasingly recognised as a recommended option for patients. This study aims to evaluate the budget impact associated with introducing a new intravenous (IV) iron, ferric derisomaltose (Monofer® [IIM]) as one of the treatment options for the management of ID in the Ministry of Health Malaysia (MOHM) setting. Methods: A 5-year budget impact model was developed from 2020 to 2024 for patients with ID that require a high iron dose (≥500 mg), using the perspective of MOHM. The model was built with four external medical specialists, each with experience and deep knowledge of ID management, to support estimations on the future development of iron use in Malaysia. Results: Compared to the current market mix with the existing IV iron products (i.e., iron sucrose and iron dextran), a cost-saving of MYR 53,910 could be achieved with the introduction of IIM in 2020. The uptake of IIM into MOHM over five years is estimated to lead to an overall budget saving of MYR 11,837,524 over a 5-year time horizon. Conclusion: The use of IIM in place of the current IV iron products in MOHM resulted in a significant cost saving by reducing the number of visits required to achieve the targeted iron dose and the shorter IV infusion time with IIM. References: Muñoz M, Gómez-Ramírez S, Besser M, Pavía J, Gomollón F, Liumbruno G. Current misconceptions in diagnosis and management of iron deficiency. Blood Transfus. 2017;15:422-37. Bouri S, Martin J. Investigation of iron deficiency anaemia. Clinical Medicine. 2018;18:242-4. Dasgupta I, Shroff R, Bennett-Jones D, Mcveigh G. Management of Hyperphosphataemia in Chronic Kidney Disease: Summary of National Institute for Health and Clinical Excellence (NICE) Guideline. Nephron Clinical Practice. 2019;124:1-9. Heidenreich P, Bozkurt B, Aguilar D, Allen L, Byun J, Colvin M. AHA/ACC/HFSA guideline for the management of heart failure: A report of the American College of Cardiology/ American Heart Association joint committee on clinical practice guidelines. Circulation. 2022. 2022;145:e895-e1032. Dignass A, Gasche C, Bettenworth D, Birgegård G, Danese S, Gisbert J. European consensus on the diagnosis and management of iron deficiency and anaemia in inflammatory bowel diseases. J Crohns Colitis. 2015;9:211-22. Rodgers G, Gilreath J. The role of intravenous iron in the treatment of anemia associated with cancer and chemotherapy. Acta Haematol. 2019;142:13-20. Means R. Iron deficiency and iron deficiency anemia: Implications and impact in pregnancy, fetal development, and early childhood parameters. Nutrients. 2020;12:447. Auerbach M, Georgieff M. Guidelines for iron deficiency in pregnancy: hope abounds: Commentary to accompany: UK guidelines on the management of iron deficiency in pregnancy. Br J Haematol. 2020;188:814-6. Muñoz M, Acheson A, Auerbach M, Besser M, Habler O, Kehlet H. International consensus statement on the peri-operative management of anaemia and iron deficiency. Anaesthesia. 2017;72:233-47. Muñoz M, Acheson A, Bisbe E, Butcher A, Gómez-Ramírez S, Khalafallah A. An international consensus statement on the management of postoperative anaemia after major surgical procedures. Anaesthesia. 2018;73:1418-31. Meybohm P, Richards T, Isbister J, Hofmann A, Shander A, Goodnough L. Patient blood management bundles to facilitate implementation. Transfus Med Rev. 2017;31:62-71. Philip K, Sadaka A, Polkey M, Hopkinson N, Steptoe A, Fancourt D. The prevalence and associated mortality of non-anaemic iron deficiency in older adults: a 14 years observational cohort study. Br J Haematol. 2020;189:566-72. Schrage B, Rübsamen N, Schulz A, Münzel T, Pfeiffer N, Wild P. Iron deficiency is a common disorder in general population and independently predicts all-cause mortality: results from the Gutenberg Health Study. Clin Res Cardiol. 2020;109:1352-7. Auerbach M, Gafter-Gvili A, Macdougall I. Intravenous iron: a framework for changing the management of iron deficiency. Lancet Haematol. 2020 Apr;7:e342-e350. Pharmacoeconomics guideline for Malaysia. 2019;. Azmi M, Junidah R, Mariam S, Safiah A, Fatimah M, Norimah S, A. Body mass index (BMI) of adults: Findings of the Malaysian Adult Nutrition Survey (MANS). Malays J Nutr. 2009;15:97-119. Ganzoni A. Dextran Antibodies, Complement Conversion and Circulating Immune Complexes After Intravenous Iron Dextran Therapy in Dialysed Patients. Nephrology Dialysis Transplantation.. Koch T, Myers J, Goodnough L. Intravenous iron therapy in patients with iron deficiency anemia: Dosing considerations. Anemia. 2015;763576. General A. s Chambers of Malaysia (AGCM). Fees (Medical). A. 2014. 2014;363. Public Service Department of Malaysia (PSDM).. Service Circular No. 12 of 2016: Amendment to the Medical Officer Service Scheme and the Dental Officer Service Scheme. Pindaan Skim Perkhidmatan Pegawai Perubatan dan Skim Perkhidmatan Pegawai Pergigian. Tahun 2016. 2016;. PSDM. Nurse [Jururawat] [Internet].. Putrajaya: PSDM. 2020. 2020 Aug 27;. Fell L, Zawada A, Rogacev K, Seiler S, Fliser D, Heine G. Distinct immunologic effects of different intravenous iron preparations on monocytes. Nephrol Dial Transplant. 2014;29:809-22. Fell L, Seiler-Mußler S, Sellier A, Rotter B, Winter P, Sester M. Impact of individual intravenous iron preparations on the differentiation of monocytes towards macrophages and dendritic cells. Nephrol Dial Transplant. 2016;31:1835-45. Bhandari S. A hospital-based cost minimisation study of the potential financial impact on the UK health care system of introduction of iron isomaltoside 1000. Ther Clin Risk Manag. 2011;7:103-13. Pollock R, Muduma G. A budget impact analysis of parenteral iron treatments for iron deficiency anemia in the UK: reduced resource utilisation with iron isomaltoside 1000. Clinicoecon Outcomes Res. 2017;9:475-83. Kalra P, Bhandari S. Efficacy and safety of iron isomaltoside (Monofer(®)) in the management of patients with iron deficiency anemia. Int J Nephrol Renovasc Dis. 2016;9:53-64. Auerbach M, Henry D, Derman R, Achebe M, Thomsen L, Glaspy J. A prospective, multi-center, randomised comparison of iron isomaltoside 1000 versus iron sucrose in patients with iron deficiency anemia; the FERWON-IDA trial. Am J Hematol. 2019;94:1007-14. Pollock R, Biggar P. Indirect methods of comparison of the safety of ferric derisomaltose, iron sucrose and ferric carboxymaltose in the treatment of iron deficiency anemia. Expert Rev Hematol. 2020;13:187-95. Foroutan N, Tarride J, Xie F, Mills F, Levine M. A comparison of pharmaceutical budget impact analysis (BIA) recommendations amongst the Canadian Patented Medicine Prices Review Board (PMPRB), public and private payers. Pharmacoecon Open. 2019;3:437-51. Hamm R, Blauvelt C, Wang E, Srinivas S. Effectiveness of antepartum intravenous iron sucrose: dose timing and impact on outcomes. The Journal of Maternal-Fetal & Neonatal Medicine. 2019;34:1983-90.